The larvae of three Greek species of Hydropsyche (Trichoptera: Hydropsychidae) and key for larvae of known Aegean Hydropsyche species - Karaouzas, Ioannis (Zootaxa, 2018)
The larvae of Hydropsyche cetibeli Malicky & Sipahiler 1993 from the Aegean, Hydropsyche mostarensis Klapálek 1898, endemic of the Balkan Peninsula, and Hydropsyche pygmalion Malicky 2001 endemic of Serifos Island (Cyclades, Greece) are described for the first time. The diagnostic features of the species are described and illustrated, and some information regarding their ecology is included. In addition, a tabular key for larvae of the known Hydropsyche species of Greece and the Aegean Islands is included.